2022
DOI: 10.1038/s41586-022-04835-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of NSP6 in the biogenesis of the SARS-CoV-2 replication organelle

Abstract: SARS-CoV-2, like other coronaviruses, builds a membrane-bound replication organelle to enable RNA replication 1 . The SARS-CoV-2 replication organelle is composed of double-membrane vesicles (DMVs) that are tethered to the endoplasmic reticulum (ER) by thin membrane connectors 2 , but the viral proteins and the host factors involved remain unknown. Here we identify the viral non-structural proteins (NSPs) that generate the SARS-CoV-2 replication organelle. NSP3 and NSP4 generate the DMVs, whereas NSP6, through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(138 citation statements)
references
References 37 publications
9
111
0
Order By: Relevance
“…We found that the interactome of NSP4, NSP6, M, ORF7A, and ORF7B significantly enriched the term of nuclear outer membrane-ER membrane network ( Fig. 3 C), consistent with that M protein was a well-known membrane protein and recent findings showing that NSP4 and NSP6 were membrane proteins of double-membrane vesicles (DMVs) ( Ricciardi et al, 2022 ). The results suggest that ORF7A and ORF7B were most likely proteins preferred to localize at the membrane, especially ORF7A containing a potential transmembrane domain ( Samavarchi-Tehrani et al, 2020 ).…”
Section: Resultssupporting
confidence: 87%
“…We found that the interactome of NSP4, NSP6, M, ORF7A, and ORF7B significantly enriched the term of nuclear outer membrane-ER membrane network ( Fig. 3 C), consistent with that M protein was a well-known membrane protein and recent findings showing that NSP4 and NSP6 were membrane proteins of double-membrane vesicles (DMVs) ( Ricciardi et al, 2022 ). The results suggest that ORF7A and ORF7B were most likely proteins preferred to localize at the membrane, especially ORF7A containing a potential transmembrane domain ( Samavarchi-Tehrani et al, 2020 ).…”
Section: Resultssupporting
confidence: 87%
“…Six variants of SARS-CoV-2, namely Alpha, Beta, Gamma, Eta, Iota and Lambda have a three aminoacid residues deletion event (ΔSGF, in positions 106–108) during evolution, in the predicted second and longest nsp6 luminal loop, and have higher zippering activity, which in turn increases transmissibility, infectivity and immune escape of the virus. Moreover, viral nsp6 acts as an organizer of DMV clusters and mediates a contact with lipid droplets (LDs) through LD-tethering complex DFCP1-RAB18 [ 36 ]. Available evidence demonstrates that the RO and the LD contacts are important players in the development and progression of viral infection via utilization of released fatty acids from LD generated by lipophagy, as an energy source for morphogenesis of progeny virions [ 37 ].…”
Section: Major Therapeutic Targets In Inhibition Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…The nsp6 is transmembrane protein (Thomas, 2021) and act as an organizer of DMV clusters mediated through lipid droplet-derived lipids. The properly formed nsp6 connectors and lipid droplets are required for the replication of SARS-CoV-2 (Ricciardi et al 2022). Nsp6 also induce in ammatory cell death in lung epithelial cells (Sun et al 2022).…”
Section: Nsp6mentioning
confidence: 99%